Economic approaches to legal reasoning and interpretation - Bix, Brian, 1962- (Economic approaches to law ;, 2018)
This insightful research review provides analysis of the most important contemporary work by experts in the economic analysis of legal reasoning and interpretation. It explores a wide range of topics in the field, from constitutional to statutory interpretation, precedent and the interpretation of contracts. The articles discussed raise key questions concerning the optimal construction of institutions, the best approach to judicial decision-making, and the best strategies for statutory and contract drafting. This fascinating review will be valuable to academics interested in legal reasoning, economic analysis and legal philosophy.